Chapter 7 Fighting Fossil Fuels Around the World - Finkeldey, Jasper (Taylor & Francis, 2023)
Fighting Global Neo-Extractivism: Fossil-Free Social Movements in South Africa analyses social struggles over damaging new fossil-fuel projects in the Global South with a focus on South Africa, Africa's biggest fossil fuel emitter. Fossil-fuel extraction in South Africa has reached a new accelerated phase in which the fossil-fuel frontier is moving beyond historical 'sacrifice zones' into non-traditional spaces, such as conservation parks and middle-class neighbourhoods, and provoking fervent opposition from grassroots activists. This book examines campaigns such as Frack Free South Africa and Save our iMfolozi Wilderness, viewing them as struggles against neo-extractivism driven by the state and industry. Through a series of detailed case studies, it highlights the shaping of mobilisation patterns by prior land use practices and the capacity to mobilise different social groups across race and class. Developing the notion of the fossil-fuel frontier as the material and political boundary that activists in South Africa and elsewhere in the world render visible, this volume provides a theoretical framework to understanding global mobilisation patterns. This timely and impassioned book will appeal to students and researchers interested in a range of subjects, including environmentalism, social movements, political ecology, and development studies.